Suitability of Stone Dust as an Alternative Aggregate in Asphalt Mixtures Using Rothfuch’s Method of Aggregate Combination - Samuel Edet Bassey (International Journal of Environmental Noise and Pollution Control, 2024)
The increase in pollution across the globe is one crucial area requiring mitigation. The bye product of quarries can pose great health and environmental risks. Construction industries in Nigeria heavily relies on conventional asphalt aggregate for construction of road pavements. This is one area of interest as mineral fillers and different aggregate gradations have a great effect on the mechanical property of asphalt concrete pavements. Stone dust is obtained from quarries across the country is relatively cheaper than the conventional river sand which is becoming depleted and scarce. The use of stone dust is a major initiative on developing the infrastructures such as express highways, power projects, ports, and harbors, to meet the requirements of globalization, in the construction of pavements and other structures concrete plays the key role and a large quantum of concrete is being utilized in every construction practices. The use of stone dust in concrete not only improve the quality of concrete but also conserve the natural river sand for future generations. In the present investigation, an evaluation on the methodology of aggregate is considered using Rothfuch method.
Keywords: Asphalt Aggregate; Bituminous Material; Filler; Morphology; Optimum Replacement; Rheology; Stone dust; Waste and Recycled Materials